Evaluation of Antibiotics Used in Pediatric Outpatients with Acute Respiratory Infection at a Private Hospital in Yogyakarta - Margaretha Wulan Kurniasari; Titien Siwi Hartayu (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2024)
Ensuring patient safety and optimal health outcomes in the healthcare system requires appropriate and rational use of medicines. One of the prescription issues noted in the pediatric clinic at a private hospital is the high use of antibiotics for acute respiratory infections. This study aimed to improve antibiotics used in outpatient pediatric clinic. This study was a descriptive analysis with a cross-sectional study design, combining quantitative and qualitative methods. The population was all prescriptions in January - March 2023. By using a purposive sampling method, there were 340 prescriptions obtained. The instruments of the study were data collection sheets and in-depth interview guidelines. Data were analyzed using the triangulation method. The antibiotic prescription rate was 64% (n=340). There were patients with Azithromycin and Erythromycin who received antibiotics below the dosing recommendations. Observation of patients’ treatment process showed that prescribers did not always suggest the laboratory examinations. Based on in-depth interviews of prescribers, they prescribed antibiotics based on the patient’s clinical examination. Based on in-depth interviews with the hospital managers, there was a tendency to choose a strategy which was a combination of educational and managerial strategies. The strategies to improve the quality of the antibiotics used include conducting training programs for the prescribers and developing standard treatment guidelines.